Stable Dyonic Thin-Shell Wormholes in Low-Energy String Theory - Ali Övgün; Kimet Jusufi (Advances in High Energy Physics)
Considerable attention has been devoted to the wormhole physics in the past 30 years by exploring the possibilities of finding traversable wormholes without the need for exotic matter. In particular, the thin-shell wormhole formalism has been widely investigated by exploiting the cut-and-paste technique to merge two space-time regions and to research the stability of these wormholes developed by Visser. This method helps us to minimize the amount of the exotic matter. In this paper, we construct a four-dimensional, spherically symmetric, dyonic thin-shell wormhole with electric charge Q, magnetic charge P, and dilaton charge Σ, in the context of Einstein-Maxwell-dilaton theory. We have applied Darmois-Israel formalism and the cut-and-paste method by joining together two identical space-time solutions. We carry out the dyonic thin-shell wormhole stability analyses by using a linear barotropic gas, Chaplygin gas, and logarithmic gas for the exotic matter. It is shown that, by choosing suitable parameter values as well as equation of state parameter, under specific conditions, we obtain a stable dyonic thin-shell wormhole solution. Finally, we argue that the stability domain of the dyonic thin-shell wormhole can be increased in terms of electric charge, magnetic charge, and dilaton charge.